Pyoderma gangrenosum: A clinico- therapeutic profile of patients attending a tertiary care hospital in Nepal - Kharel, C; Agrawal, S; Rijal, A; Bhattarai, S (Journal of College of Medical Sciences-Nepal, 2012)
Pyoderma gangrenosum (PG) is a primarily sterile inflammatory neutrophilic dermatosis characterized by recurrent cutaneous ulcerations with mucopurulent or hemorrhagic exudate. In many cases, PG is associated with inflammatory bowel disease, rheumatic disorder or neoplasia. The peak of incidence occurs between the ages of 20 to 50 years with women being more often affected than men. To study the clinical and therapeutic profile of patients with pyoderma gangrenosum. All patients diagnosed as pyoderma gangrenosum in the department of dermatology from July 14th 2003- July 12th 2008 were included in the study. Demographic profile, clinical features as well as relevant investigations, treatment and follow-up were noted. A total of 8 patients with pyoderma gangrenosum were diagnosed over a 5 year period. There were 3 males and 5 female patients whose ages ranged from 32 to 80 years. Lower limbs were the commonest site to be involved in 6 patients (75%). Recurrent episodes were noted in 4 patients (50%) and among them 3 patients (75%) had multiple ulcers. Histopathological confirmation of the diagnosis was done in 7 patients (87.5%). Association with ulcerative colitis was seen in 2 patients (25%). All patients were treated with dapsone and systemic steroids which showed resolution of the lesions in all patients. Pyoderma gangrenosum was seen more frequently in females and association with ulcerative colitis was seen in 25% of the patients. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 29-35 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6823